2018
DOI: 10.1007/s12560-018-9340-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Ready-to-Eat Meat Products for Hepatitis E Virus in Switzerland

Abstract: Seroprevalence data for pig herds suggested that there must be a relevant reservoir for hepatitis E virus (HEV) in Switzerland. To know more about the viral presence in ready-to-eat meat products, we screened pork liver sausages and raw meat sausages from the Swiss retail market for the presence of HEV. Testing was performed with a detection method where the virus extraction step was optimized. As for the performance of the improved method, the mean recovery rate for the mengovirus process control was 24.4%, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
(44 reference statements)
1
31
0
Order By: Relevance
“…Another study had screened ready-to-eat meat products for Hepatitis E virus. Positive rates of 18.9% for liver sausages and 5.7% for raw meat sausages were estimated [ 138 ].…”
Section: Different Routes Of Transmissionmentioning
confidence: 99%
“…Another study had screened ready-to-eat meat products for Hepatitis E virus. Positive rates of 18.9% for liver sausages and 5.7% for raw meat sausages were estimated [ 138 ].…”
Section: Different Routes Of Transmissionmentioning
confidence: 99%
“…Human HEV infection, investigated using seroprevalence studies, was found to be more prevalent in older ages [7][8][9][10][11][12][13][14][15][16][17][18][19][20], lower socio-economic status [21], poorer residence areas [9,[14][15], among sheltered homeless adults [22] or uneducated people [14], specific nationalities (for example, higher in mixed race donors and ethnic groups within China [12,15], or in immigrants from Afghanistan [14]), drinking water from wells or rivers [15], consumption of meat products [7,15,17,23] especially pork [24,25] and following blood transfusions [1].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that nonporcine transmission modes are possible and cannot be ruled out completely. However, the risk of infection remains highest through dietary sources where viral loads are known to be sufficiently large to cause an infection . Some other signs also point towards a dietary source.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of infection remains highest through dietary sources where viral loads are known to be sufficiently large to cause an infection. 39 Some other signs also point towards a dietary source. Amongst the three main ethnic groups present in Singapore, the HEV incidence rate in Chinese was twice the rate in Indians and nearly 10 times the rate in Malays.…”
Section: Discussionmentioning
confidence: 99%